HAK MILIK DALAM ISLAM PERSPEKTIF IBN TAYMIYAH - IYOH MASTHIYAH (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
According to Ibn Taymi’yah, rights are a strength that base on syariah in the utility of an object. However, this strength is various in terms of its form and stage. At once, this strength makes an individual has the right to sell or to rent, or to present, or to lease, or to utilize for productive purposes on a condition that the right is incomplete because it is limited. Based on this view, Ibn Taymiyah devides rights in Islam into three; individual right, social right or collective, and nasional right.